An Incidental Finding of Azygos Lung Lobe - Arsia Hanif; Sana Shahid; Niaz Hussain Soomro; Ummalqura Sarosh; Sana Jawed (ziauddin University, 2024)
An azygos lobe of a lung, a rare anomaly or anatomical variant of the lung formed during embryogenesis when the posterior cardinal vein deviates from its normal migration path. Clinically, azygos lobe can imitate various ailments. Most commonly, it is found incidentally and usually involved the right lung. 'Azygos' means 'an unpaired structure' in the Greek language. Discussed here, is a rare case of a 35-year-old patient who presented with symptoms of a lung hydatid cyst but was incidentally diagnosed with azygos lobe on the computed tomography scan. The imaging findings were confirmed intraoperatively during the excision of the ruptured hydatid cyst of the lung. It is crucial for physicians to know about this rare anatomical variant of the lung to avoid a misdiagnosis. It is even more important for thoracic surgeons to be aware of an azygos lobe of the lung so they can predict and avoid its associated complications during thoracic surgery. Keywords: Azygos Vein; Lung; Hydatid Cyst; Thoracic Surgery.